An investigation into the potential association between nutrition and Alzheimer’s disease - He, Mingyue; Lian, Tenghong; Liu, Zhan; Li, Jinghui; Qi, Jing; Li, Jing; Guo, Peng; Zhang, Yanan; Luo, Dongmei; Guan, Huiying; Zhang, Weijia; Zheng, Zijing; et al. (Frontiers in Nutrition, 2024)
Background Malnutrition is the most common nutritional issue in Alzheimer's disease (AD) patients, but there is still a lack of comprehensive evaluation of the nutritional status for AD patients. This study aimed to determine the potential association of a range of nutritional indices for AD at different stages.Methods Subjects, including individuals with normal cognition (NC) and patients diagnosed with AD, were consecutively enrolled in this cross-sectional study.Demographics, body composition, dietary patterns, nutritional assessment scales and nutrition-related laboratory variables were collected. Binary logistics regression analyses and receiver operating characteristic (ROC) curves were used to indicate the association between nutrition-related variables and AD at different stages.Results Totals of 266 subjects, including 73 subjects with NC, 72 subjects with mild cognitive impairment due to AD (AD-MCI) and 121 subjects with dementia due to AD (AD-D) were included. There was no significant difference in dietary patterns, including Mediterranean diet and Mediterranean-DASH diet intervention for neurodegenerative delay (MIND) diet between the three groups. Lower BMI value, smaller hip and calf circumferences, lower Mini Nutritional Assessment (MNA) and Geriatric Nutritional Risk Index (GNRI) scores, and lower levels of total protein, albumin, globulin, and apolipoprotein A1 were associated with AD (all P < 0.05).Total protein and albumin levels had the greatest ability to distinguish AD from non-AD (AUC 0.80, 95% CI 0.74 -0.84, P < 0.001), increased by combining calf circumference, MNA score and albumin level (AUC 0.83, 95% CI 0.77 -0.88, P < 0.001). Albumin level had the greatest ability to distinguish NC from AD-MCI (AUC 0.75, 95% CI 0.67 -0.82, P < 0.001), and MNA score greatest ability to distinguish AD-MCI from AD-D (AUC 0.72, 95% CI 0.65 -0.78, P < 0.001).Nutritional status of AD patients is significantly compromised compared with normal controls, and tends to be worsened with AD progresses. Early identification and intervention of individuals with nutritional risk or malnutrition may be significantly beneficial for reducing the risk, development, and progression of AD.